Resubmission of Contractor's All Risk (CAR) insurance - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding resubmission of Contractor's All Risk (CAR) insurance of BRAC University new campus project.